Encyclopaedia of mass media - Khan, M. A. (Himalaya Books, 2010)
In modern times, Mass Media is one of the most vital sectors in any society or economy. Mass media can be used for various purposes, like `advocacy1 for both business and social concerns. Enrichment and education - traditionally through performances like acting, music, and sports along with reading and Public Service announcements. Another aspect of Mass Media is mainstream media, which implies ability to transmit tacit knowledge,with a bias - political or otherwise, - towards favouring a certain individual outcome or resolution of an event. This view of central media can be contrasted with la.